Crowd Funding for Orphan Drugs: The Case of Baby Pia - Pinxten, Wim (Frontiers in Pharmacology, 2021)
Medical crowdfunding is a relatively new strategy to obtain access to orphan drugs. The case of Baby Pia, a Belgian girl with SMA type 1 for whom in 2018 more than 2,1 million was raised to get her treated with Zolgensma®, illustrates well the potential power of medical crowdfunding. But apart from the success in raising money, the case is also of particular importance for the ethical issues it brings to the surface as related to justice, equity, power imbalances, responsibility, accountability, indebtedness and privacy.